2.2.129 Problems 12801 to 12900

Table 2.259: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

12801

\[ {}y+x +y^{\prime } x = 0 \]

[_linear]

2.434

12802

\[ {}6 x -2 y+1+\left (2 y-2 x -3\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.570

12803

\[ {}\sec \left (x \right ) \cos \left (y\right )^{2}-\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0 \]

[_separable]

7.101

12804

\[ {}\left (x +1\right ) y^{2}-x^{3} y^{\prime } = 0 \]

[_separable]

1.575

12805

\[ {}2 \left (1-y^{2}\right ) x y+\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime } = 0 \]

[_separable]

21.224

12806

\[ {}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0 \]

[_separable]

3.522

12807

\[ {}x \,{\mathrm e}^{\frac {y}{x}}+y-y^{\prime } x = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

10.569

12808

\[ {}2 x^{2} y+3 y^{3}-\left (x^{3}+2 x y^{2}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

22.274

12809

\[ {}y^{2}-x y+x^{2} y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

2.429

12810

\[ {}2 x^{2} y+y^{3}-x^{3} y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

88.555

12811

\[ {}y^{3}+x^{3} y^{\prime } = 0 \]

[_separable]

4.067

12812

\[ {}x +y \cos \left (\frac {y}{x}\right )-x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

5.849

12813

\[ {}4 x +3 y+1+\left (x +y+1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.465

12814

\[ {}4 x -y+2+\left (x +y+3\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.472

12815

\[ {}2 x +y-\left (4 x +2 y-1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.969

12816

\[ {}y+2 x y^{2}-x^{2} y^{3}+2 x^{2} y y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Riccati]

1.964

12817

\[ {}2 y+3 x y^{2}+\left (x +2 x^{2} y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

9.149

12818

\[ {}y+x y^{2}+\left (x -x^{2} y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.815

12819

\[ {}y^{\prime }+y \cot \left (x \right ) = \sec \left (x \right ) \]

[_linear]

1.681

12820

\[ {}y^{\prime } x +\left (x +1\right ) y = {\mathrm e}^{x} \]

[_linear]

1.355

12821

\[ {}y^{\prime }-\frac {2 y}{x +1} = \left (x +1\right )^{3} \]

[_linear]

1.532

12822

\[ {}\left (x^{3}+x \right ) y^{\prime }+4 x^{2} y = 2 \]

[_linear]

1.309

12823

\[ {}x^{2} y^{\prime }+\left (1-2 x \right ) y = x^{2} \]

[_linear]

1.724

12824

\[ {}\left (-x^{2}+1\right ) y^{\prime }-2 \left (x +1\right ) y = y^{{5}/{2}} \]

[_rational, _Bernoulli]

1.781

12825

\[ {}y y^{\prime }+x y^{2} = x \]

[_separable]

2.043

12826

\[ {}\sin \left (y\right ) y^{\prime }+\sin \left (x \right ) \cos \left (y\right ) = \sin \left (x \right ) \]

[_separable]

40.056

12827

\[ {}4 y^{\prime } x +3 y+{\mathrm e}^{x} x^{4} y^{5} = 0 \]

[_Bernoulli]

1.725

12828

\[ {}y^{\prime }-\frac {1+y}{x +1} = \sqrt {1+y} \]

[[_1st_order, _with_linear_symmetries]]

3.558

12829

\[ {}x^{4} y \left (3 y+2 y^{\prime } x \right )+x^{2} \left (4 y+3 y^{\prime } x \right ) = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

5.897

12830

\[ {}y^{2} \left (3 y-6 y^{\prime } x \right )-x \left (y-2 y^{\prime } x \right ) = 0 \]

[_separable]

2.245

12831

\[ {}2 x^{3} y-y^{2}-\left (2 x^{4}+x y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.724

12832

\[ {}y^{2}-x y+x^{2} y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

2.395

12833

\[ {}\frac {-y+y^{\prime } x}{\sqrt {x^{2}-y^{2}}} = y^{\prime } x \]

[‘y=_G(x,y’)‘]

1.942

12834

\[ {}x +y-\left (x -y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.588

12835

\[ {}x^{2}+y^{2}-2 x y y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

8.154

12836

\[ {}x -y^{2}+2 x y y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

1.865

12837

\[ {}-y+y^{\prime } x = x^{2}+y^{2} \]

[[_homogeneous, ‘class D‘], _rational, _Riccati]

1.660

12838

\[ {}3 x^{2}+6 x y+3 y^{2}+\left (2 x^{2}+3 x y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.175

12839

\[ {}2 x +\left (x^{2}+y^{2}+2 y\right ) y^{\prime } = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.243

12840

\[ {}y^{4}+2 y+\left (x y^{3}+2 y^{4}-4 x \right ) y^{\prime } = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

2.986

12841

\[ {}x^{3} y-y^{4}+\left (x y^{3}-x^{4}\right ) y^{\prime } = 0 \]

[_separable]

1.633

12842

\[ {}y^{2}-x^{2}+2 m x y+\left (m y^{2}-m \,x^{2}-2 x y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

8.523

12843

\[ {}y^{\prime } x -y+2 x^{2} y-x^{3} = 0 \]

[_linear]

1.572

12844

\[ {}\left (x +y\right ) y^{\prime }-1 = 0 \]

[[_homogeneous, ‘class C‘], [_Abel, ‘2nd type‘, ‘class C‘], _dAlembert]

1.709

12845

\[ {}x +y y^{\prime }+y-y^{\prime } x = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.581

12846

\[ {}y^{\prime } x -a y+b y^{2} = c \,x^{2 a} \]

[_rational, _Riccati]

2.749

12847

\[ {}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0 \]

[_separable]

2.822

12848

\[ {}\sqrt {1-y^{2}}+\sqrt {-x^{2}+1}\, y^{\prime } = 0 \]

[_separable]

16.403

12849

\[ {}y^{\prime }-x^{2} y = x^{5} \]

[_linear]

2.011

12850

\[ {}\left (y-x \right )^{2} y^{\prime } = 1 \]

[[_homogeneous, ‘class C‘], _dAlembert]

2.612

12851

\[ {}y^{\prime } x +y+x^{4} y^{4} {\mathrm e}^{x} = 0 \]

[_Bernoulli]

3.412

12852

\[ {}\left (1-x \right ) y+\left (1-y\right ) x y^{\prime } = 0 \]

[_separable]

1.416

12853

\[ {}\left (y-x \right ) y^{\prime }+y = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.015

12854

\[ {}-y+y^{\prime } x = \sqrt {x^{2}+y^{2}} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

6.560

12855

\[ {}-y+y^{\prime } x = \sqrt {x^{2}-y^{2}} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

57.979

12856

\[ {}x \sin \left (\frac {y}{x}\right )-y \cos \left (\frac {y}{x}\right )+x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

4.121

12857

\[ {}x -2 y+5+\left (2 x -y+4\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.072

12858

\[ {}y^{\prime }+\frac {y}{\left (-x^{2}+1\right )^{{3}/{2}}} = \frac {x +\sqrt {-x^{2}+1}}{\left (-x^{2}+1\right )^{2}} \]

[_linear]

3.379

12859

\[ {}\left (-x^{2}+1\right ) y^{\prime }-x y = a x y^{2} \]

[_separable]

2.160

12860

\[ {}x y^{2} \left (3 y+y^{\prime } x \right )-2 y+y^{\prime } x = 0 \]

[[_homogeneous, ‘class G‘], _rational]

5.063

12861

\[ {}\left (x^{2}+1\right ) y^{\prime }+y = \arctan \left (x \right ) \]

[_linear]

1.968

12862

\[ {}5 x y-3 y^{3}+\left (3 x^{2}-7 x y^{2}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.450

12863

\[ {}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2} \]

[_linear]

2.250

12864

\[ {}x y^{2}+y-y^{\prime } x = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.181

12865

\[ {}\left (1-x \right ) y-\left (1+y\right ) x y^{\prime } = 0 \]

[_separable]

1.356

12866

\[ {}3 x^{2} y+\left (x^{3}+x^{3} y^{2}\right ) y^{\prime } = 0 \]

[_separable]

2.731

12867

\[ {}\left (x^{2}+y^{2}\right ) \left (x +y y^{\prime }\right ) = \left (x^{2}+y^{2}+x \right ) \left (-y+y^{\prime } x \right ) \]

[_rational]

2.868

12868

\[ {}2 x +3 y-1+\left (2 x +3 y-5\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.805

12869

\[ {}y^{3}-2 x^{2} y+\left (2 x y^{2}-x^{3}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

28.628

12870

\[ {}2 x^{3} y^{2}-y+\left (2 x^{2} y^{3}-x \right ) y^{\prime } = 0 \]

[_rational]

1.594

12871

\[ {}\left (x^{2}+y^{2}\right ) \left (x +y y^{\prime }\right )+\sqrt {1+x^{2}+y^{2}}\, \left (y-y^{\prime } x \right ) = 0 \]

[[_1st_order, _with_linear_symmetries]]

2.528

12872

\[ {}1+{\mathrm e}^{\frac {y}{x}}+{\mathrm e}^{\frac {x}{y}} \left (1-\frac {x}{y}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

5.187

12873

\[ {}y^{\prime } x +y-y^{2} \ln \left (x \right ) = 0 \]

[_Bernoulli]

2.042

12874

\[ {}x^{3} y^{4}+x^{2} y^{3}+x y^{2}+y+\left (x^{4} y^{3}-x^{3} y^{2}-x^{3} y+x \right ) y^{\prime } = 0 \]

[_rational]

3.040

12875

\[ {}\left (2 \sqrt {x y}-x \right ) y^{\prime }+y = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

93.860

12876

\[ {}{y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+x y = 0 \]

[_quadrature]

1.782

12877

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.297

12878

\[ {}y^{2}+{y^{\prime }}^{2} = 1 \]

[_quadrature]

0.556

12879

\[ {}\left (2 y^{\prime } x -y\right )^{2} = 8 x^{3} \]

[_linear]

0.558

12880

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2} = 1 \]

[_quadrature]

0.224

12881

\[ {}{y^{\prime }}^{3}-\left (2 x +y^{2}\right ) {y^{\prime }}^{2}+\left (x^{2}-y^{2}+2 x y^{2}\right ) y^{\prime }-\left (x^{2}-y^{2}\right ) y^{2} = 0 \]

[_quadrature]

3.400

12882

\[ {}2 y^{\prime } x -y+\ln \left (y^{\prime }\right ) = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

2.393

12883

\[ {}4 x {y^{\prime }}^{2}+2 y^{\prime } x -y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

2.057

12884

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.313

12885

\[ {}y^{\prime }+2 x y = x^{2}+y^{2} \]

[[_homogeneous, ‘class C‘], _Riccati]

1.855

12886

\[ {}y = -y^{\prime } x +x^{4} {y^{\prime }}^{2} \]

[[_homogeneous, ‘class G‘], _rational]

1.988

12887

\[ {}{y^{\prime }}^{2}+2 y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

0.421

12888

\[ {}x +y^{\prime } y \left (2 {y^{\prime }}^{2}+3\right ) = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

5.016

12889

\[ {}a^{2} y {y^{\prime }}^{2}-2 y^{\prime } x +y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.394

12890

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.279

12891

\[ {}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries]]

7.257

12892

\[ {}\left (-y+y^{\prime } x \right )^{2} = {y^{\prime }}^{2}+1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

0.547

12893

\[ {}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 y^{\prime } x -1 = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(y)]‘]]

7.461

12894

\[ {}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 \,{\mathrm e}^{2 x} y^{\prime }-{\mathrm e}^{2 x} = 0 \]

[[_homogeneous, ‘class C‘], _dAlembert]

1.046

12895

\[ {}{\mathrm e}^{2 y} {y^{\prime }}^{3}+\left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x} = 0 \]

[‘y=_G(x,y’)‘]

299.631

12896

\[ {}x y^{2} {y^{\prime }}^{2}-y^{3} y^{\prime }+x = 0 \]

[[_homogeneous, ‘class G‘], _rational]

10.450

12897

\[ {}\left (x^{2}+y^{2}\right ) \left (1+y^{\prime }\right )^{2}-2 \left (x +y\right ) \left (1+y^{\prime }\right ) \left (x +y y^{\prime }\right )+\left (x +y y^{\prime }\right )^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

4.037

12898

\[ {}y = 2 y^{\prime } x +y^{2} {y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries]]

107.704

12899

\[ {}a^{2} y {y^{\prime }}^{2}-2 y^{\prime } x +y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.421

12900

\[ {}\left (x -y^{\prime }-y\right )^{2} = x^{2} \left (2 x y-x^{2} y^{\prime }\right ) \]

[‘y=_G(x,y’)‘]

80.129